Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ciamis - Bella Juliantika Sujana; Erlan Suwarlan; Ii Sujai (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
This research is motivated by the existence of problems related to the Implementation of the Standards for Measurement of DPRD Oversight Activities in Population Administration Services at the Population and Civil Registration Service which are caused by the measurement of activities in the implementation of DPRD supervision work visits that have not run optimally. This study aims to find out more about the results of analyzing the Oversight Function so that it can run optimally. The method used in this research is a qualitative research method. Data collection techniques were carried out by observation, interviews, documentation, and literature studies. Data analysis techniques in this study started from data reduction, data presentation, and drawing conclusions. Based on the results of the research, it is known that the DPRD's oversight function in Adminduk Services has been running, seen from the dimensions of setting supervision standards, comparing supervision standards with the results of work implementation and corrective actions. However, it has not run optimally seen from the dimensions of measuring the implementation of the work in terms of direct observation and inspection indicators in the field. Seeing the point of problems in the Service when there are problems, immediately looking for solutions to solve them. The DPRD's supervisory function in Adminduk Services based on the dimensions of the supervisory function includes: Observation and direct inspection in the field have not run optimally. In measuring and assessing work results, having standard measurement tools, oral and written reports, deviations, factors causing deviations, changing standards, and changing measurement activities have been running optimally.